EFFECTIVENESS OF STINGLESS BEE HONEY IN INCREASING COLLAGEN IN THE SKIN WOUND HEALING OF RATS - Maulana, M Ridha; Gunanti, Gunanti; Subangkit, Mawar (Jurnal Kedokteran Hewan, 2025)
The purpose of this study was to determine the effectiveness of stingless bee honey in healing incision wounds on rat skin based on collagen formation. A total of 30 Sprague-Dawley rats were divided into 3 observation days (n= 10 rats). The incisions performed on all rats but given different treatments. In negative control group, the incision wound was not treated, while in positive control, the incision was treated with bioplacentom. Rats in treatment 1 and treatment 2, the incision wound were treated with 75% and 100% stingless bee honey treatment was given once a day for 7 days. The results showed that the 75% and 100% stingless bee honey groups showed a significant effect on reducing the wound length and increasing the collagen density (P0.05). As conclusion, stingless bee honey is effective in increasing collagen density in the wound healing process of rat.